On the relationships linking intrinsic and extrinsic sense of freedom with pro-environmental attitudes. Synergic and buffering effects of the identification with all humanity - Urbańska, Beata; Radkiewicz, Piotr; Uram, Patrycja (Frontiers in Psychology, 2022)
This study aimed to examine whether the individual way of understanding freedom is related to pro-environmental attitudes. This idea has not been studied before. Based on E. Fromm's (1941) and I. Berlin's (1969) division between negative and positive freedom, the concept of an extrinsic and intrinsic sense of freedom, was recently introduced. In the paper, the authors examined whether understanding freedom as extrinsic (absolute and unconditional) was related to a decrease in environmental concern and pro-environmental behavior, while understanding it as intrinsic (conditional, limited by the needs of other people) had the opposite effect. Another set of hypotheses concerned the moderating role of identification with all humanity (IWAH). The authors hypothesized that in people with a high level of IWAH, the positive relationship between intrinsic freedom and pro-environmental attitudes was stronger, and the negative relationship between extrinsic freedom and pro-environmental attitudes was weaker compared to people with a low level of IWAH. The study was conducted on a sample of 773 Polish young adults (18-29 years) using a professional research panel. The results provide empirical evidence that intrinsic and extrinsic way of understanding freedom is related to environmental concern and pro-environmental behavior. Moreover, the hypothesis concerning the moderating role of IWAH was confirmed. These results contribute to a better understanding of the factors that determine commitment to climate protection.